Microphotoluminescence (μPL) measurements of bidimensional materials in a custom-made setup. (May 2019) - Di Girolamo, F.V.; Di Lieto, A.; Sottile, A.; Roddaro, S.; Tonelli, M.; Tredicucci, A.
Abstract: The continuously growing interest in the so called bidimensional (2D) materials has been accompanied by a parallel development of techniques specifically devoted to manipulating and measuring micro-sized objects. Here a flexible microphotoluminescence ( μ PL) custom-made setup has been built on purpose: every setup component has been optimized for 2D materials; an automatized system able to perform measurements in different positions of the sample and execute mapping have been made; the dependence of the μ PL intensity, peak center and other properties such as the Full Width Half Maximum (FWHM) on the position has been then extracted. The attention has been focused on WS 2 and phosphorene. Optical response has been compared between Chemical Vapor Deposition (CVD) grown WS 2 transferred on graphene and sapphire, especially focusing on the changes in the trion peak. Signatures have been found that can be attributed to photoluminescence from thick (more than five layers) phosphorene flakes.